TINGKAT KEBERHASILAN INSEMINASI BUATAN (IB) SAPI MADURA DI DESA BINAAN BUJUR TIMUR KECAMATAN BATUMARMAR - Umam, Siful; Riszqina, Riszqina (Universitas Madura, 2024)
This research was conducted to determine the success rate of Artificial Insemination (IB) of Madura Cattle in East Longitude Assisted Village, Batumarmar District, the research method used a survey. A sample of 50 heads was determined purposively based on Madura cattle that were ready to be mated at the study location. The observed variables are Service Per Conception (S/C), and Conception Rate (CR). The results showed that from the number of cows in IB 50 heads in IB I gardening as many as 43, while IB II as many as 7 heads succeeded in the success rate of Artificial Insemination (IB) of Madura Cattle in East Longitude Assisted Village, Batumarmar District, showing an S / C value of 1.14 and a CR value in Madura Cattle of 86%. The conclusion of this study is that for each average pregnancy requires 1.14 straw doses,. The CR number in the livestock group is influenced by the magnitude of the average S / C value, if the lower the S / C, the higher the CR will be.